GERAKAN ANTI STUNTING DAN PEMANFAATAN PRODUK OLAHAN MAKANAN PENDAMPING UNTUK IBU DAN ANAK DI DESA TATAH LAYAP KAB. BANJAR KALIMANTAN SELATAN - Dwi Rizki Febrianti; Dhelsy Saniyya Afifa; Rahmayanti Azizah; Nazulla Mujib Nararia; Asmiati Nurul Hikmah; As’syifa Rahmah (Jurnal Bakti untuk Negeri, 2023)
One of the children's problems related to the fulfillment of nutrition that can have a negativeimpact on the quality of life and growth and development of a child is stunting. The purpose ofthis community service is to provide education and increase the knowledge of parents, youth,and posyandu cadres and play an active role in preventing stunting. The method used consistsof several stages such as field observation, planning, field action consisting of outreach,pretest and posttest, education and product creation. The results of the pretest and posttestvalues for community service proved that there was a significant increase from 62% to 96%regarding community knowledge about the prevention and dangers of stunting. Thesocialization and education carried out has succeeded in helping to increase the knowledgeof the people of Tatah Layap Village. The activity of making products also gives positive resultsto the community because it makes them interested in trying to process products that areefficacious for preventing stunting in children.